Anti–pan-neurofascin IgG3 as a marker of fulminant autoimmune neuropathy. Issue 5 (September 2019) - Stengel, Helena; Vural, Atay; Brunder, Anna-Michelle; Heinius, Annika; Appeltshauser, Luise; Fiebig, Bianca; Giese, Florian; Dresel, Christian; Papagianni, Aikaterini; Birklein, Frank; Weis, Joachim; Huchtemann, Tessa; et al.
Abstract : Objective: To identify and characterize patients with autoantibodies against different neurofascin (NF) isoforms. Methods: Screening of a large cohort of patient sera for anti-NF autoantibodies by ELISA and further characterization by cell-based assays, epitope mapping, and complement binding assays. Results: Two different clinical phenotypes became apparent in this study: The well-known clinical picture of subacute-onset severe sensorimotor neuropathy with tremor that is known to be associated with IgG4 autoantibodies against the paranodal isoform NF-155 was found in 2 patients. The second phenotype with a dramatic course of disease with tetraplegia and almost locked-in syndrome was associated with IgG3 autoantibodies against nodal and paranodal isoforms of NF in 3 patients. The epitope against which these autoantibodies were directed in this second phenotype was the common Ig domain found in all 3 NF isoforms. In contrast, anti–NF-155 IgG4 were directed against the NF-155–specific Fn3Fn4 domain. The description of a second phenotype of anti–NF-associated neuropathy is in line with some case reports of similar patients that were published in the last year. Conclusions: Our results indicate that anti–pan-NF-associated neuropathy differs from anti–NF-155-associated neuropathy, and epitope and subclass play a major role in the pathogenesis and severity of anti–NF-associated neuropathy and should be determined to correctly classify patients, also in respect to possible differences in therapeutic response.